Logika Fuzzy dengan Metode Mamdani dalam Menentukan Tingkat Peminatan Tipe Motor Honda - Jufriadi (SAFE-Network, 2021)
Honda motorcycles are in demand by the public as a cheap means of land transportation. CV Hayati is the main motorcycle dealer company in Padang. In carrying out its activities, CV Hayati needs to consider several factors when selling motorcycles that are in demand by consumers. However, CV Hayati still uses manual means in looking at the interest in the motor that will be purchased by consumers. To solve the problem, a system is needed that can help with decision-making by consumers in purchasing motors according to their interests. In this study, the decision to buy a motor that consumers were interested in was done using the fuzzy logic of mamdani method. With the decision-making system in motor interest, it is expected to help and facilitate consumers in determining the motor they are interested in buying. The results of this study can be viewed using the PHP programming language and MySQL database, with the fuzzy logic of the mamdani method. Where in the fuzzyfication process consider several input variables namely: price, oil fuel tank capacity, engine speed, baggage capacity and vehicle weight. So that by defuzzification can be determined the recomedation of motors that are in demand by consumers.